Large A.C. machines : theory and investigation methods of currents and losses in stator and rotor meshes including operation with nonlinear loads - Boguslawsky, Iliya; Korovkin, Nikolay; Hayakawa, Masashi (Springer, 2017)
In this monograph the authors solve the modern scientific problems connected with A.C. motors and generators, based first on the detailed consideration of their physical phenomena. The authors describe the theory and investigative methods they developed and applied in practice, which are considered to be of essential interest for specialists in the field of the electrical engineering industry in European countries, the USA, Argentina, and Brazil, as well as in such countries as India, China, and Iran. This book will be of interest to engineers specialized in the field of the manufacture, operation, and repair of A.C. machines (motors and generators) as well as electric drives; to professors, lecturers, and post-graduate students of technical universities, who are specializing in the field of electric machine engineering and electric drives; and to students who are engaged in the field of high current techniques, electric drives, and electric machine engineering.
Keywords: Electric machinery -- Alternating current.; elektronické knihy; electronic books